Tratamento fisioterapêutico de pacientes após fratura distal de rádio durante a fase ambulatorial - CAMPOS, Fernanda Aparecida (2019)
This dissertation contains two studies that were developed during the master's degree. Study 1: A systematic review with meta-analysis was performed initially. The title of the article is "Supervised Physiotherapy vs. Home Program After Distal Radius Fracture: Systematic Review and Meta-Analysis" and aims to assess current literature to determine if a home-based program is more effective than supervised physical therapy for patients after fracture of the distal radius. distal radio. We conclude that the two interventions are valid as long as the professional knows how to evaluate the best for his patient with distal radius fracture. Study 2: A functional evaluation study was carried out. The title of the manuscript is "Functional evaluation of patients submitted to surgical treatment of Radio Distal Fracture" and aims to verify the comparison between the fracture side and the contralateral limb for the measures of range of motion, muscular strength, muscular activity and fatigue in patients after six months postoperatively of radio distal fracture; to verify if there is an association between the force measurements and electromyographic measurements in the patients after six months postoperatively of distal radius fracture; and verify if there is an association between the positive and negative affection Scale Scales, Kinesiophobia Cover Scale, Patient-Rated Wrist Evaluation and pain catastrophic scale with force and electromyography measures. We conclude that there is a difference between the fracture side and the contralateral limb for the measures of range of motion of wrist extension, muscle strength, muscular activity and fatigue in patients after six months postoperatively of distal radius fracture. It presented a positive correlation of association between electromyography measurements, dynamometry and the scales evaluated.